Avaliação da audição em criança de 3 a 6 anos, em creches e pré-escolas municipais, de São José do Rio Preto, SP - Piatto, Vânia Belintani (1998)
The aim of this study was to evaluate the hearing and the prevalence of hearing impairment among children, in the age groups of 3 to 6 years old, from Municipal Nursery and Pre-schools of São José do Rio Preto, S.P. At first stage, audiometries in a free field were performed for screening in 103 children, both sexes in 8 Nursery and 8 Pre-schools previously selected. At second stage, the ones who presented audiometric alterations were referred to the Phonoaudiological Service of FAMERP to perform conventional pure tone audiometer. The classification of hearing impairment in relation to grade was made according to W.H.O. approaches. A male child (0.97%) was found with light grade of conductive hearing impairment in the left ear ( LE=35 dB). There was no significant difference among the ratio of hearing impairment in both sexes (p=1.00). Nine children (8.73%) showed alterations in the hearing thresholds by air conduction in 4000, 6000 and/or 8000 Hz sharp frequencies. The ratio among alterations in these frequencies was not statistically significant in both sexes (p=1.00). There is need of further studies to evaluate the result found in children with alterations in those sharp frequencies. The found prevalence of hearing impairment in this studied population can chek the need of use of prevention programs and earlier diagnosis of hearing impairments.